Cloud Cost Optimization for Social Impact: Automating FinOps for Non-Profits - Sridhar Sampath (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
This article explores the emerging field of cloud cost optimization for mission-driven organizations, examining how non-profits can leverage FinOps automation to redirect technology investments toward social impact. Organizations can transform cloud expenditures from administrative overhead into strategic mission enablers by adapting commercial FinOps principles to the unique constraints of resource-limited environments. The article identifies key implementation strategies, including infrastructure right-sizing, automated resource hygiene, effective credit management, and mission-aligned cost allocation frameworks. Through case studies of successful implementations, the article demonstrates how technical efficiencies directly translate to enhanced program delivery. A phased implementation roadmap provides a pragmatic approach for organizations with limited technical resources, while knowledge-sharing strategies and collaborative models create sustainable FinOps practices. The article concludes by examining future trends, including AI-assisted optimization and community-based approaches, highlighting how cloud cost management represents not merely a cost-cutting exercise but a fundamental realignment of technology resources with mission objectives. This article contributes to the growing field of technology management for social impact, offering practical guidance for non-profit leaders seeking to maximize the value of their cloud investments.